High-resolution cyclic framework for the Songliao Basin in northeastern China, and its implications for sedimentation and organic matter enrichment - Xinrui Wang; Yu Sun; Limin Yu; Zhenxing Tang; Baiquan Yan; Ruhao Liu (Frontiers in Earth Science)
The study of fine-grained sedimentation has consistently concentrated on investigating the mechanisms and principles governing the enrichment of organic matter. However, the lack of unified stratigraphic framework has always existed as fine-grained sedimentation covers two distinct grain-size grades, namely, mud and silt, which has impeded the progress of subsequent production research. This study exemplified this issue by analyzing the first member of the Qingshankou Formation in the southern Songliao Basin. We established reconstructed gamma and density curves that mitigated filter noise interference, integrated high-resolution sequence results with astronomical cycle divisions, and created a high-frequency isochronous stratigraphic framework for clastic fine-grained sedimentation by leveraging the weak sensitivity of sandstone density curves and the robust stability in eccentricity cycle extraction. This approach addresses the inconsistencies in stratigraphic division methodologies and mismatched outcomes stemming from the use varying techniques to delineate mud and silt components within clastic fine-grained sedimentary sequences. Furthermore, it elucidates how tectonic-scale variations in sediment supply coupled with potential accommodation changes dictate macroscopic stacking patterns within strata, whereas climate fluctuations on orbital time scales govern sand-mud progradation degrees within these layers, culminating in periodic rhythmic characteristics characterized by vertical sand-mud interbedding. A model for stratigraphic development pertaining to lake delta systems constrained by a “synchronous heterotopy” paradigm is proposed for the southern Songliao Basin. The organic matter enrichment pattern aligns with its filling dynamics, indicating an “overfilling” type developmental pattern at lower strata levels where organic material predominantly originates from terrestrial plant debris external to the basin; this material accumulates primarily within silty zones along layers—with areas exhibiting heightened enrichment values slightly lagging behind short-eccentric maxima positions. In contrast, under an upper “balanced filling” type developmental framework, sources of organic matter are derived both internally and externally relative to the basin—exhibiting substantial heterogeneity—and regions marked by elevated organic matter concentrations are directly associated with locations identified as short-eccentric maxima.